User experience of an institutional repository: A study of OpenUCT with a focus on postgraduate students - Kalimashe, Hanoria (Department of Knowledge and Information Stewardship, 2024)
An institutional repository (IR) plays a significant role in meeting users' information needs by providing access to the institution's intellectual outputs. The literature revealed that although studies on IRs have been conducted there is limited research on their user experience (UX). UX is gaining significant traction in academic libraries as it is becoming more useful to assess the services of the library from a user-centred perspective. The study investigated the user experience of OpenUCT from the postgraduate (PG) students' perspective. The study determined the extent to which the students are aware of the IR, their expectations of, and attitudes towards the IR, the utilisation of the IR and usability challenges in relation to its use. The study used a qualitative research method to achieve the research objective. Semi-structured interviews and structured observations were used to gather data from twelve Masters students at the Graduate School of Business (GSB) department in the Faculty of Commerce at the University of Cape Town. A group of students whose course has a dissertation element were selected for interviews and observation. The participants included students who were in the beginning, middle and final stages of their dissertation. Data was also collected through an interview with a key informant at the UCT Library department. The findings revealed that half of the participants knew about OpenUCT and were utilising the IR, whereas the other half was not aware of its existence. The study also revealed that the IR does meet most of their expectations and needs, although there were some areas where they felt their expectations were not met. The participants generally had positive attitudes towards the IR. However, the findings also revealed that students had negative attitudes regarding functionality. There were issues related to navigability, the usability of the OpenUCT user interface, findability, and accessibility of its content. Issues included difficulty in retrieving and locating content, the irrelevance of search results, poor presentation, inconsistency of content records and lack of specific search filters and fields that the participants thought would be useful when searching content. Other issues were duplication of search fields and content records, lack of clear visibility and transparency of outputs offered in the IR Communities. The study closes with recommendations on how those involved with IR and OpenUCT can proactively deal with these student concerns.